Carbon Constraints in the Fourteenth and Twenty-first Centuries - Hoffmann, Volker; Busch, Timo (Journal of industrial ecology, 2007)
Fourteenth century and twenty-first century carbon constraints are compared. The low availability of carbon constrains the activities of the islanders. Fossil resources are naturally limited and scarcity is determined by factors namely endowment of natural stocks, access to reserves, and technical developments that postpone final depletion. From the input perspective, carbon constraints are related to the disposition of fossil resources. From the outer perspectives, carbon constraints are related to climate change. The strong interrelation of firms due to material flow exchanges makes a symbiosis more vulnerable to external shocks. A key challenge is to identify and adopt technological innovations that reduce the carbon exposure of firms. It is suggested that the carbon-related uncertainties shall be analyzed in detail when designing interfirm collaborations.